Low surface energy coating for solder drop protection and method of making, solder drop protection method, cleaning method and applications
Patent Information
- Application Number
- CN202611203921.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-13
AI Technical Summary
本发明要解决的技术问题是现有的防护材料的高温稳定性不足导致防护失效、清除困难易损伤基材、难以适用于复杂几何形状的零件表面的问题
1.砜基和氟元素的协同改性使涂层表面能极低,该涂料能在短时间(2h内)高温(1100℃以下)情况下对焊渣液滴等具有良好的疏水性,使焊渣与金属零件的结合力低,有效阻止焊料润湿和铺展,焊渣清除更加容易,从根本上解决焊料滴落问题。
Smart Images

Figure CN122898210A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of welding protection technology, and more specifically, to a low surface energy coating for solder drip protection, a method for preparing the coating, a method for protecting against solder drips, a method for removing the drips, and its application. Background Technology
[0002] In the manufacturing of high-end equipment such as aero-engines and gas turbines, brazing is a key process for joining high-temperature alloy components (such as turbine guide vanes). During brazing, liquid brazing filler metal (such as BNi-2 series nickel-based brazing filler metal) fills the weld seam under capillary action, but at the same time, it is very prone to unnecessary flow and dripping along non-welded areas (such as pinholes, gaps, narrow channels, fixture surfaces, etc.), causing the following problems: 1. Solder waste: Dripping solder cannot participate in effective bonding, increasing production costs; 2. Component contamination: Solder adheres to non-soldering surfaces, affecting the appearance of the component and the accuracy of subsequent machining; 3. Difficult to clean: After high-temperature brazing, the solidified brazing filler metal is tightly bonded to the substrate. Mechanical removal can easily damage the surface of the parts, while chemical removal may corrode the substrate material. 4. Decreased yield: For precision parts with complex internal cavity structures, solder blockage of critical areas such as air film pores and cooling channels will lead to part scrap. Existing technologies commonly use solder drip protection methods including: mechanical blocking (such as metal baffles and ceramic plugs), coating with magnesium oxide / alumina paste, and pre-applied flow-blocking agents.
[0003] However, these methods have many shortcomings: mechanical blocking components are difficult to adapt to complex curved surfaces and tiny holes; traditional slurry coatings are prone to cracking and peeling at high temperatures, resulting in protective failure; most flow-blocking agents are for single use and the removal process is cumbersome, and some residues may even react adversely with the substrate.
[0004] Therefore, there is an urgent need to develop a new type of solder drip protection material and supporting method, which should remain stable in the high-temperature environment of brazing, have excellent low surface energy characteristics to prevent solder wetting and spreading, and be easy to remove completely after brazing without damaging the substrate. Summary of the Invention
[0005] (a) Technical problems to be solved The technical problem to be solved by the present invention is that the existing protective materials have insufficient high-temperature stability, which leads to protective failure, are difficult to clean and easily damage the substrate, and are difficult to apply to the surface of parts with complex geometries.
[0006] (II) Technical Solution To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a low surface energy coating for solder drip protection, comprising the following components: sulfone-modified organosilicon heat-resistant resin, heat-resistant functional filler, alcohol solvent, and additives; the heat-resistant functional filler comprises at least one of submicron-sized titanium dioxide powder, silica powder, and alumina powder; the additives comprise a silane coupling agent; wherein the sulfone-modified organosilicon heat-resistant resin is prepared by the following method: trimethylsilyl ester, glycerol, trifluoroethanol, and maleic anhydride are sequentially added to a reaction vessel, xylene is added for dehydration, and the reaction is carried out at 105-120°C for 120-150 min. The system temperature is then raised to 160-180°C and the reaction continues for 90-120 min. After the reaction is completed, the temperature is lowered to 40-60°C, and acetone is added to adjust the solid content of the system to 40-45%. The present invention significantly reduces the surface energy of the coating by introducing sulfone groups (-SO2-) and fluorine elements (from trifluoroethanol) to modify the organosilicon resin, thereby giving it excellent repellency against molten solder. Meanwhile, the high bond energy of the sulfone group and the heat-resistant framework of the organosilicon backbone endow the coating with structural stability at high temperatures of 900-1100℃.
[0007] Preferably, the heat-resistant functional filler is composed of titanium suboxide powder, silica powder, and alumina powder, with a mass ratio of 0:5:5 or 5:2:3. Different filler ratios allow for control of the coating color: a 5:5 mass ratio of titanium suboxide to alumina results in a black coating, suitable for visual contrast under optical inspection environments; a 5:5 mass ratio of silica to alumina results in a transparent coating with a pale yellow tint, which does not affect visual inspection of the substrate surface. Furthermore, submicron-sized fillers can fill the gaps in the resin network, improving coating density and erosion resistance.
[0008] Preferably, based on 1L of alcohol solvent, the content of each component is as follows: 230-250g of sulfone-modified organosilicon heat-resistant resin, 20-40g of alumina, 16-20g of titanium suboxide powder or silica powder, and 9g of silane coupling agent; the mass-to-volume ratio of the total solid components to the alcohol solvent is 275-295g:1L. This formulation ensures the coating has suitable viscosity and solid content, with the Coating 4 cup viscosity controlled at 20-30s, facilitating spraying and brushing operations, while ensuring that the target thickness is achieved in a single coat.
[0009] Preferably, the amount of the silane coupling agent added is 8% of the total mass of the heat-resistant functional filler. The silane coupling agent forms a chemical bridge between the inorganic filler and the organic resin, enhances the cohesion of the coating, and avoids protective failure caused by filler detachment at high temperatures.
[0010] Secondly, the present invention also provides a method for preparing the aforementioned low surface energy coating, comprising the following steps: S1. Mix the components of the anti-stick coating material according to any one of claims 1-6 evenly, and stir or shake to form a uniform dilute solution coating. S2. Apply the dilute solution coating obtained in step S1 to the parts to be brazed that require protection by air spraying or brushing; the spraying parameters are: spray gun diameter 1.3mm, spraying distance 120-130mm, spraying pressure 0.3-0.4MPa. S3. The coated parts to be brazed are cured at room temperature to 100℃ for 2-96 hours to form a solid coating with a thickness of 1-8μm; the coating thickness is 1-4μm in narrow gaps and inaccessible areas, and 3-8μm in areas where brazing solder drips severely or where the brazing temperature is higher than 1000℃.
[0011] This method is simple to operate, requires no special equipment, and can be quickly implemented in a workshop environment. By controlling the combination of curing temperature and time, it can adapt to the needs of different production cycles.
[0012] Preferably, the curing conditions in step S3 are any of the following: curing at 35°C for about 90 hours, curing at 50°C for about 24 hours, curing at 55°C for about 4 hours, curing at 60°C for about 3 hours, and curing at 100°C for about 2 hours. Multiple curing paths are available to flexibly adapt to different working conditions.
[0013] Preferably, in step S2, the brushing method is as follows: using a brush to apply paint, five coats are applied to areas prone to dripping solder droplets, and one coat is applied to areas less prone to dripping. By varying the number of coats, the local thickness can be controlled.
[0014] Thirdly, this invention also provides a method for preventing solder dripping. A low surface energy coating prepared using the above method is applied to the surface of small holes, gaps, narrow channels, or fixtures of brazed parts, followed by brazing at 900–1100°C for no more than 2 hours. Within this temperature and time range, the coating maintains a stable low surface energy state, and the contact angle of the molten solder on its surface is greater than 100°, preventing it from wetting and spreading, thus effectively blocking it from the non-welding area. After brazing, the coating naturally powders due to the decomposition of its organic components, facilitating subsequent removal.
[0015] Fourthly, this invention also provides a method for removing low surface energy coatings used for solder droplet protection, comprising the following steps: first, removing large residual solder droplets from the surface using hand tools; then, polishing with sandpaper; finally, immersing in a NaOH solution with a concentration of 20-30 wt% and a temperature of 70-80°C for 30-40 minutes; after removal, ultrasonic cleaning and drying are performed to complete the removal of coating residue. Since the coating has partially powdered after high-temperature brazing, the alkaline solution can quickly dissolve the residual silica framework and filler particles, and has no corrosive effect on the nickel-based superalloy substrate, achieving non-destructive removal.
[0016] Fifthly, the present invention also provides the application of the low surface energy coating for solder drip protection, the low surface energy coating prepared by the preparation method, the solder drip protection method, or the method for removing the low surface energy coating in the protection of nickel-based cast superalloy brazing solder drips. In particular, the above technical solutions are especially suitable for the brazing process of complex thin-walled structural components such as turbine guide vanes and turbine rotor blades made of nickel-based cast superalloys of grades K403, K417, and K418, and can effectively protect critical parts such as film cooling holes, cooling channels, and tenons from solder contamination.
[0017] (III) Beneficial Effects The above-described technical solution of the present invention has at least the following advantages: 1. The synergistic modification of sulfone and fluorine elements results in an extremely low surface energy of the coating. This coating exhibits excellent hydrophobicity to slag droplets and other materials under high temperature (below 1100℃) conditions within a short period (within 2 hours), resulting in low adhesion between the slag and the metal parts. This effectively prevents solder wetting and spreading, making slag removal easier and fundamentally solving the problem of solder dripping.
[0018] 2. The coating is an alcohol-based dilute solution system that can be applied to surfaces of any complex shape by spraying or brushing, including deep holes, narrow crevices, blind cavities and other areas that are difficult to handle by traditional methods. It can be applied over a large area and is faster and more efficient than paste-like coatings.
[0019] 3. By adjusting the number of coating passes and spraying parameters, different coating thicknesses (1-8μm) can be achieved in different areas of the same part, balancing protective effect and economy.
[0020] 4. This coating can be either transparent or black. If transparent (using more submicron fillers such as silica), it can be applied to parts without removal if strict removal requirements are not specified, having minimal impact on the thickness, weight, appearance, and performance of the component. If high removal requirements are specified, the coating can be formulated as black, making the application location more clearly visible and improving visual inspection. After brazing, the coating naturally powders and can be completely removed by soaking in an alkaline solution and simple mechanical wiping, without damaging the high-temperature alloy substrate, thus solving the long-standing industry problem of difficult slag removal.
[0021] 5. This coating can be stored under normal conditions, with relatively relaxed storage requirements. Traditional water-repellent coatings often contain flammable, explosive, or toxic solvents and must be stored separately according to fire safety requirements. The raw materials are widely available and inexpensive; the alcohol solvent is non-toxic and volatile; and the alkaline cleaning solution can be neutralized before discharge. The overall process is green and environmentally friendly. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 These are surface state diagrams of the parts to be brazed from different perspectives provided in the embodiments of the present invention.
[0024] Figure 2 These are surface state diagrams of the parts to be brazed from different perspectives after being coated with a low surface energy coating, provided in an embodiment of the present invention.
[0025] Figure 3 These are surface state diagrams of parts after brazing from different perspectives, provided in embodiments of the present invention.
[0026] Figure 4 This is a schematic diagram of the state of a brazed part coated with a low surface energy coating immersed in NaOH solution, as provided in an embodiment of the present invention. Detailed Implementation
[0027] To make the technical problems, solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0028] The specific implementation of the present invention will be described in more detail below with reference to specific embodiments: Example 1: When preparing the coating, weigh the following components according to the following ratio: 230 g / L sulfone-modified organosilicon heat-resistant resin, 20 g / L submicron-sized alumina, 16 g / L submicron-sized titanium dioxide (titanium black) powder, 9 g / L graft modifier (silane coupling agent), and 1 L alcohol solvent. The particle size of the heat-resistant functional filler should be controlled to <1 μm. The ratio of solids (heat-resistant functional filler and graft modifier) to alcohol solvent should be 275 g: 1 L, ensuring a viscosity between 20-30 s / Ford cup 4. Store at -5℃ until use. The preparation method of sulfone-modified organosilicon heat-resistant resin is as follows: trimethylsilyl ester, glycerol, trifluoroethanol and maleic anhydride are added sequentially to a reaction vessel, and xylene is added for dehydration. The reaction is then carried out at 105-120℃. After the reaction has been carried out for 120-150 min, the system temperature is raised to 160-180℃ and the reaction is continued for 90-120 min. After the reaction is completed, the temperature is lowered to 40-60℃, and an appropriate amount of acetone is added to adjust the solid content of the system to 40-45%, thus obtaining the above-mentioned sulfone-modified organosilicon heat-resistant resin.
[0029] During coating preparation, the liquid coating is directly shaken or poured into a container and mechanically stirred for 5 minutes and then filtered through gauze. When the solution is relatively uniform, it is suitable for spraying. Then, the coating is loaded into the spray gun canister, the pressure is adjusted to 0.3 MPa, and sprayed from a distance of 120 mm from the surface of the workpiece to be sprayed using a 1.3 mm diameter air spray gun. After the coating is sprayed, it is allowed to air dry naturally for 15 minutes and then cured at 50℃ for 4 hours before it can be used directly.
[0030] During brazing, K403 turbine guide vanes were used as the weld material, and BNi-2(C) powder was used as the brazing filler metal between the turbine guide vanes. The amount of BNi-2(C)-S brazing filler metal used was no less than twice the maximum volume of the weld gap, and the melting temperature of the brazing filler metal was set between 980℃ and 1020℃. Brazing was carried out in a vacuum furnace at a vacuum pressure of 1×10⁻⁶. -3 Pa, argon purging, argon partial pressure greater than 100 Pa (flow), brazing conditions 1070℃ / 10min.
[0031] Post-brazing treatment: Remove the turbine guide vanes, immerse them in a 20wt.% NaOH solution at 80℃ for 30 minutes, then ultrasonically clean them with water or ethanol for 8 minutes, and finally dry them to remove any remaining surface coating.
[0032] Example 2: When preparing the coating, weigh the following components according to the following ratio: 250 g / L sulfone-modified organosilicon heat-resistant resin, 20 g / L submicron-sized alumina, 16 g / L submicron-sized titanium dioxide (titanium black) powder, 9 g / L graft modifier (silane coupling agent), and 1 L alcohol solvent. The particle size of the submicron-sized heat-resistant functional filler should be controlled to <1 μm. The ratio of solids (heat-resistant functional filler and graft modifier) to alcohol solvent should be 295 g: 1 L, ensuring a viscosity between 20 s and 30 s / Ford cup 4. Store at -5℃ until use. The preparation method of sulfone-modified organosilicon heat-resistant resin is as follows: trimethylsilyl ester, glycerol, trifluoroethanol and maleic anhydride are added sequentially to a reaction vessel, and xylene is added for dehydration. The reaction is then carried out at 110-120℃. After the reaction has been carried out for 140-150 min, the system temperature is raised to 170-180℃ and the reaction is continued for 110-120 min. After the reaction is completed, the temperature is lowered to 50-60℃, and an appropriate amount of acetone is added to adjust the solid content of the system to 40-45%, thereby obtaining the above-mentioned sulfone-modified organosilicon heat-resistant resin.
[0033] During coating preparation, shake the liquid paint directly or pour it into a container and mechanically stir for 6 minutes, then filter it with gauze. When the solution is relatively uniform, it is suitable for spraying. Then, fill the paint into the spray gun canister, adjust the pressure to 0.4 MPa, and spray using a 1.3 mm diameter air spray gun at a distance of 130 mm from the surface to be sprayed. After the paint is sprayed, allow it to air dry naturally for 25 minutes, then perform heat preservation and curing. After curing at 60℃ for 3 hours, it can be used directly. Alternatively, use a brush to apply the slurry to the surface of areas prone to dripping weld beads, applying 5 coats to areas prone to dripping and 1 coat to areas not prone to dripping.
[0034] During brazing, K403 turbine guide vanes were used as the weld material, and BNi-2(C) powder was used as the brazing filler metal between the turbine guide vanes. The amount of BNi-2(C)-S brazing filler metal used was no less than twice the maximum volume of the weld gap. The experiment was conducted in a vacuum furnace at a vacuum pressure of 2 × 10⁻⁶. -3 The process is carried out under argon purging, with an argon partial pressure greater than 200 Pa (flow), and the brazing conditions are 1080℃ / 10min.
[0035] Post-brazing treatment: Remove the turbine guide vanes, immerse them in a 30wt.% NaOH solution at 80℃ for 40 minutes, then ultrasonically clean them with water or ethanol for 8 minutes, and finally dry them to remove any surface coating residue.
[0036] Example 3: When preparing the coating, weigh the following components according to the following proportions: 230 g / L sulfone-modified organosilicon heat-resistant resin, 40 g / L submicron-sized alumina, 16 g / L submicron-sized white silica powder, 9 g / L graft modifier (silane coupling agent), and 1 L alcohol solvent. The particle size of the submicron-sized heat-resistant functional filler should be controlled to <1 μm. The ratio of solids (heat-resistant functional filler and graft modifier) to alcohol solvent should be 295 g: 1 L, ensuring a viscosity between 20-30 s / Ford cup 4. Store at -5°C until use. The preparation method of sulfone-modified organosilicon heat-resistant resin is as follows: trimethylsilyl ester, glycerol, trifluoroethanol and maleic anhydride are added sequentially to a reaction vessel, and xylene is added for dehydration. The reaction is then carried out at 110-120℃. After the reaction has been carried out for 140-150 min, the system temperature is raised to 170-180℃ and the reaction is continued for 110-120 min. After the reaction is completed, the temperature is lowered to 50-60℃, and an appropriate amount of acetone is added to adjust the solid content of the system to 40-45%, thereby obtaining the above-mentioned sulfone-modified organosilicon heat-resistant resin.
[0037] During coating preparation, shake the liquid paint directly or pour it into a container and mechanically stir for 5 minutes, then filter it with gauze. When the solution is relatively uniform, it is suitable for spraying. Then, fill the paint into the spray gun canister, adjust the pressure to 0.3 MPa, and spray using a 1.3 mm diameter air spray gun at a distance of 120 mm from the surface to be sprayed. After the paint is sprayed, allow it to air dry naturally for 40 minutes, then perform heat preservation and curing. After curing at 55℃ for 4 hours, it can be used directly. Alternatively, use a brush to apply the slurry to the surface of areas prone to dripping weld beads, applying 5 coats to areas prone to dripping and 1 coat to areas not prone to dripping.
[0038] During brazing, K403 turbine guide vanes were used as the weld material, and BNi-2(C) powder was used as the brazing filler metal between the turbine guide vanes. The amount of BNi-2(C)-S brazing filler metal used was no less than twice the maximum volume of the weld gap. The experiment was conducted in a vacuum furnace at a vacuum pressure of 1×10⁻⁶. -3 Pa, argon purging, argon partial pressure greater than 100 Pa (flow), brazing conditions 1070℃ / 10min.
[0039] Post-brazing treatment: Remove the turbine guide vanes, immerse them in a 30wt.% NaOH solution at 70℃ for 30 minutes, and then ultrasonically clean them for 5 minutes to remove any remaining surface coating.
[0040] The comparison between the low surface energy coating provided by this invention and traditional flow-blocking agents and traditional hydrophobic coatings is shown in Table 1 below: Table 1: Comparison of traditional flow-blocking agents, traditional hydrophobic coatings, and the low surface energy coating of this invention. The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A low surface energy coating for solder drip protection, characterized in that, It consists of the following components: Sulfone-modified organosilicon heat-resistant resin; The heat-resistant functional filler comprises at least one of submicron-sized sub-titanium oxide powder, silica powder, and alumina powder; Alcohol solvent; The additives include silane coupling agents; The sulfone-modified organosilicon heat-resistant resin is prepared by the following method: trimethylsilyl ester, glycerol, trifluoroethanol and maleic anhydride are added sequentially to a reaction vessel, xylene is added for dehydration, and the reaction is carried out at 105-120℃ for 120-150 min. The system temperature is then raised to 160-180℃ and the reaction is continued for 90-120 min. After the reaction is completed, the temperature is lowered to 40-60℃, and acetone is added to adjust the solid content of the system to 40-45%.
2. The low surface energy coating for solder drip protection as described in claim 1, characterized in that, The heat-resistant functional filler is composed of titanium suboxide powder, silica powder and alumina powder, with the mass ratio of titanium suboxide powder, silica powder and alumina powder being 0:5:5 or 5:2:
3.
3. The low surface energy coating for solder drip protection as described in claim 1, characterized in that, Based on 1L of alcohol solvent, the contents of each component are as follows: sulfone-modified organosilicon heat-resistant resin 230-250g, alumina 20-40g, titanium suboxide powder or silicon oxide powder 16-20g, silane coupling agent 9g; the mass-volume ratio of the total mass of solid components to the alcohol solvent is 275-295g:1L.
4. The low surface energy coating for solder drip protection as described in claim 1, characterized in that, The amount of the silane coupling agent added is 8% of the total mass of the heat-resistant functional filler.
5. A method for preparing a low surface energy coating as described in any one of claims 1 to 4, comprising the following steps: S1. Mix the components of the anti-stick coating material according to any one of claims 1-6 evenly, and stir or shake to form a uniform dilute solution coating. S2. Apply the dilute solution coating obtained in step S1 to the parts to be brazed that require protection by air spraying or brushing; the spraying parameters are: spray gun diameter 1.3mm, spraying distance 120-130mm, spraying pressure 0.3-0.4MPa. S3. The coated parts to be brazed are cured at room temperature to 100℃ for 2-96 hours to form a solid coating with a thickness of 1-8μm; the coating thickness is 1-4μm in narrow gaps and inaccessible areas, and 3-8μm in areas where brazing solder drips severely or where the brazing temperature is higher than 1000℃.
6. The preparation method according to claim 5, characterized in that, The curing conditions in step S3 are any of the following: curing at 35°C for about 90 hours, curing at 50°C for about 24 hours, curing at 55°C for about 4 hours, curing at 60°C for about 3 hours, and curing at 100°C for about 2 hours.
7. The preparation method according to claim 5, characterized in that, In step S2, the brushing method is as follows: dip a brush into the paint and brush 5 coats on the area where weld droplets are easy to drip, and brush 1 coat on the area where they are not easy to drip.
8. A method for preventing solder dripping, characterized in that, The low surface energy coating as described in any one of claims 1 to 4, prepared by the method described in claim 5, is applied to the small holes, gaps, narrow channels, or fixture surfaces of the brazed parts, followed by brazing at 900–1100°C for no more than 2 hours.
9. A method for removing a low surface energy coating for solder drip protection as described in any one of claims 1-4, characterized in that, Includes the following steps: First, use hand tools to remove large pieces of residual solder droplets from the surface, then polish with sandpaper, and finally soak in a NaOH solution with a concentration of 20-30wt% and a temperature of 70-80℃ for 30-40 minutes. After taking it out, ultrasonically clean and dry it to complete the removal of coating residue.
10. The application of a low surface energy coating for solder drip protection as described in any one of claims 1-4, a low surface energy coating prepared by the preparation method as described in claim 5, a solder drip protection method as described in claim 6, or a method for removing the low surface energy coating as described in claim 7 in the protection of solder dripping from nickel-based cast high-temperature alloys.